2019
DOI: 10.1007/s11187-019-00249-3
|View full text |Cite
|
Sign up to set email alerts
|

Skills combinations and firm performance

Abstract: Creative skills, STEM (science, technology, engineering and mathematics) skills and management skills have all been positively associated with firm performance as well as regional growth. But do firms that combine these types of skills in their workforce grow more quickly than those that do not? We compare the impact of STEM, creative and management skills on their own, and in various combinations, on turnover growth. We use a longitudinal dataset of UK firms over the period 2008-2014 with lagged turnover data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 80 publications
(93 reference statements)
2
23
0
1
Order By: Relevance
“…Hence, even within the very same firm, when management practices differ across establishments, we find large differences in productivity associated with variations in management practices. 21 This is reassuring, since we will show in Section III that there is a large amount of management variation across plants within the same firm.…”
Section: A Management and Productivitymentioning
confidence: 81%
See 1 more Smart Citation
“…Hence, even within the very same firm, when management practices differ across establishments, we find large differences in productivity associated with variations in management practices. 21 This is reassuring, since we will show in Section III that there is a large amount of management variation across plants within the same firm.…”
Section: A Management and Productivitymentioning
confidence: 81%
“…There is certainly evidence of this from the coefficient on capital, which falls dramatically when establishment fixed effects are added, which is a common result in the literature 21. Running regressions in the cross section with firm fixed effects is an even more general model as we (i) allow the coefficients on the factor inputs (and other controls) to be year-specific and (ii) we switch off the time series variation of plant-specific productivity and management within a firm.…”
mentioning
confidence: 75%
“…Recent evidence suggests that small businesses show differences in growth patterns while appearing similar in terms of organizational and environmental characteristics, such as size, sector, governance and access to finance (Hamelin, 2013;Hurst and Pugsley, 2011). Such findings are at the centre of a longstanding discussion in the entrepreneurship literature (Carland et al, 1984) about whether and how an entrepreneur's individual characteristics influence firm outcomes, including internationalization (e.g., Siepel et al, 2019).…”
Section: The Aim and Scope Of The Special Sectionmentioning
confidence: 99%
“…Given this scientific description of associative thought working in the musician’s mind, the continued mystery regarding associative thought in the innovator’s mind may finally be addressed from a new angle [ 7 ]. Recent research linking arts training of scientists and engineers to an increased capacity for finding nonobvious solutions provides initial evidence of a functional role for the arts in an arts-innovation nexus [ 11 , 12 ]. A limitation of the present research findings is that we can only posit a connection between the arts and the design/innovation processes in respondent establishments rather than directly observing this connection.…”
Section: Design Innovation and Rural Creative Places: Possibilities mentioning
confidence: 99%
“…Preliminary research also suggests that arts added to a short–course curriculum delivered to both high school students and engineering professionals to develop innovative capacity can augment participants’ ability to develop non-obvious solutions to problems [ 11 ]. A study using the UK Community Innovation Survey found that training in art skills (graphic, design, and multimedia skills) combined with science skills (math and engineering) resulted in higher levels of innovative performance [ 12 ]. Although this research is far removed from the arts-innovation discussion within economic geography it does suggest a plausible alternative hypothesis for how the arts may impact innovation.…”
Section: Introductionmentioning
confidence: 99%